Healing touch. - Mok, Shu Jing. (2009)
This documentary short titled The Healing Touch is produced by a group of graduating students from the Wee Kim Wee School of Communication and Information (WKWSCI) at the Nanyang Technological University (NTU), Singapore. The Healing Touch introduces Reiki healing, a complementary therapy, to the locals who have a surface understanding of this spiritual healing method and aims to discover the multiple perspectives towards Reiki. Besides having Reiki masters and practitioners to share their views and experiences, more scientific viewpoints are also available through interviews with experts from medical and psychological fields.